2014
DOI: 10.1016/s0187-893x(14)70065-5
|View full text |Cite
|
Sign up to set email alerts
|

Atividade antimicrobiana no combate as larvas do mosquito Aedes aegypti: Homogeneização dos óleos essenciais do linalol e eugenol

Abstract: Homogenization of essential oils of linalool and eugenol)In the search for alternative chemical control against Aedes aegypti L., various studies are developed and encouraged in order to find new substances insecticidal plant and in this context essential oils have been shown to be very promising. Extracted from the essential oils of Lindl Pimenta dioica species (leaves) and Aniba duckei Kostermans (stems) by means of hydrodistillation using a Clevenger system and promoted its mixture of equal parts. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 1 publication
0
3
0
4
Order By: Relevance
“…[46][47][48] As características de determinados grupamentos químicos estruturais desses compostos ou a combinação entre eles podem conferir aumento ou redução da atividade larvicida. [46][47][48] Essa é uma área de pesquisa que vem despertando muito interesse, tendo em vista que é necessário produzir inseticidas eficazes e seguros para a população e para o meio ambiente. 46,47 Em estudo realizado por Santos et al, 46 21 compostos apresentaram boa atividade larvicida contra o Ae.…”
Section: Compostos Naturaisunclassified
“…[46][47][48] As características de determinados grupamentos químicos estruturais desses compostos ou a combinação entre eles podem conferir aumento ou redução da atividade larvicida. [46][47][48] Essa é uma área de pesquisa que vem despertando muito interesse, tendo em vista que é necessário produzir inseticidas eficazes e seguros para a população e para o meio ambiente. 46,47 Em estudo realizado por Santos et al, 46 21 compostos apresentaram boa atividade larvicida contra o Ae.…”
Section: Compostos Naturaisunclassified
“…provoca 100 % de mortalidad (Seon-Mi et al 2009). En moscas Camptomyia corticalis Loew, 1851 (Diptera: Cecidomyiidae), por efecto fumigante alcanza 75,0 y 93,0 % de mortalidad a las concentraciones de 1,0 y 1,4 mg.cm -3 (Jun-Ran et al 2012), y la mezcla de aceite de pimienta con aceite de palo de rosa Aniba rosaeodora Ducke, 1930 (Laurales: Lauraceae), aplicado al mosquito A. aegypti se determinó la CL 50 de 11,4 % (Schalcher et al 2014). Se tienen reportes de repelencia de mosca blanca T. vaporariorum y B. tabaci, con aceites esenciales de otras plantas con efecto diverso.…”
Section: Resultados Y Discusiónunclassified
“…Además, con la concentración de 2,4 % se reduce 66,18 % la población (Bao-Liang et al 2015). Para el mosquito A. aegypti la CL 50 es de 9,086 % de eugenol (Schalcher et al 2014) y para Reticulitermes chinensis Snyder, 1949 (Isoptera: Rhinotermitidae) es de 1,21 % (Xie et al 2015), en R. speratus, otra especie de termitas, las concentraciones de 0,06 a 2,0 % de eugenol y metil eugenol causaron 100 % de mortalidad (Seon-Mi et al 2009). El eugenol a la concentración de 3,0 y 1,3 % causó toxicidad de contacto y redujo el consumo de alimento en el gorgojo del maíz S. zeamais; a 3,5 y 9,9 % disminuye el consumo de alimento en larvas y adultos de T. castaneum (Huang et al 2002).…”
Section: /12unclassified
“…Following the parameters of larvicidal activity, it showed a LC 50 of 98.06 μl.ml -1 . Pereira et al (2014), tested the essential oils of species such as Pimenta dioica and Anibaduckei against A. aegypti and concluded that the major components, eugenol and linalool are capable of providing a greater larvicidal effect to the insect. It is important to note that linalool is one of the non-major components of H. irregularis essential oil, but it may cause interactions between the other constituents and potentialize the toxic and larvicidal effect.…”
Section: Resultsmentioning
confidence: 99%